2016
DOI: 10.1001/jamaoncol.2016.1373
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Extent of Resection With Survival in Glioblastoma

Abstract: This analysis represents the largest systematic review and only quantitative systematic review to date performed on this subject. Compared with STR, GTR substantially improves overall and progression-free survival, but the quality of the supporting evidence is moderate to low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
457
3
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 810 publications
(492 citation statements)
references
References 69 publications
19
457
3
13
Order By: Relevance
“…Gross total resection has been widely shown to be prognostic for improved outcomes compared to subtotal resection in glioblastoma (27,28); however, its role in extending survival in gliosarcoma, particularly in the TMZ era, is less understood. Prior database studies in the Surveillance, Epidemiology, and End Results (SEER) Program (23,29) and the National Cancer Database (NCDB) (30,31) have suggested a potential benefit of achieving GTR.…”
Section: Discussionmentioning
confidence: 99%
“…Gross total resection has been widely shown to be prognostic for improved outcomes compared to subtotal resection in glioblastoma (27,28); however, its role in extending survival in gliosarcoma, particularly in the TMZ era, is less understood. Prior database studies in the Surveillance, Epidemiology, and End Results (SEER) Program (23,29) and the National Cancer Database (NCDB) (30,31) have suggested a potential benefit of achieving GTR.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons use ISM to maximize resection, primarily to increase the patient’s survival while minimizing the chances of morbidity and loss of neurological function [2, 24]. AC is the most frequently used form of ISM, by using electrocortical and subcortical mapping to differ eloquent brain tissue from brain or tumor tissue that is safe to resect.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with partial or subtotal resections will benefit less from radio- and chemotherapy as compared to patients with total resections [1518, 2022, 24]. Intraoperative stimulation mapping (ISM) allows the surgeon to prevent damage to eloquent cortical and subcortical areas during resection [2, 19]. There is compelling evidence that surgeons using ISM experience increased resection percentage while preserving quality of life in low-grade glioma (LGG).…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence indicates that aggressive cytoreductive surgery is associated with significantly improved survival outcomes, which could be due to surgery being influenced by the mutational status of the isocitrate dehydrogenase (IDH) gene (10)(11)(12). A previous meta-analysis based on 37 studies assessed whether greater extent of surgery affects survival outcomes in GBM patients and found that GTR is associated with significantly improved overall survival (OS) and progression-free survival (PFS) compared with subtotal resection (STR) (13). However, GTR and STR have not been comparatively assessed for their effects in elderly patients with high-grade glioma.…”
Section: Introductionmentioning
confidence: 99%